2009
DOI: 10.2353/ajpath.2009.090530
|View full text |Cite
|
Sign up to set email alerts
|

Robust Th1 and Th17 Immunity Supports Pulmonary Clearance but Cannot Prevent Systemic Dissemination of Highly Virulent Cryptococcus neoformans H99

Abstract: The present study dissected the role of a Th2 bias in pathogenesis of Cryptococcus neoformans H99 infection by comparing inhalational H99 infections in wild-type BALB/c and IL-4/IL-13 double knockout mice. H99-infected wild-type mice showed all major hallmarks of Th2 but not Th1/Th17 immunity in the lungs and lung-associated lymph nodes. In contrast, the IL-4/13 ؊/؊ mice developed robust hallmarks of Th1 and Th17 but not Th2 polarization. The IL-4/IL-13 deletion prevented pulmonary eosinophilia, goblet cell me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
190
1
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 155 publications
(198 citation statements)
references
References 47 publications
5
190
1
2
Order By: Relevance
“…Visual inspection of cytospins prepared from sorted populations confirmed that both AMs and ExMs were large cells (12)(13)(14)(15)(16)(17)(18) m) with abundant cytoplasm and round/oval nuclei ( Figure 1D). AMs displayed largely smooth cell membranes and contained few intracellular vacuoles.…”
Section: Cd11c ϩ Cd11b ϩ Autofluorescent Exms Are the Most Prevalent mentioning
confidence: 95%
“…Visual inspection of cytospins prepared from sorted populations confirmed that both AMs and ExMs were large cells (12)(13)(14)(15)(16)(17)(18) m) with abundant cytoplasm and round/oval nuclei ( Figure 1D). AMs displayed largely smooth cell membranes and contained few intracellular vacuoles.…”
Section: Cd11c ϩ Cd11b ϩ Autofluorescent Exms Are the Most Prevalent mentioning
confidence: 95%
“…In contrast, alternatively activated macrophages (AAM) harbor C. neoformans. 11,[32][33][34] Generation of CAM/AAM has been postulated to be regulated by Th1/Th2 bias; 11,22,23,30,33,35 however, differential activation of macrophages can also occur in response to other factors, such as stimulation of toll-like receptors (TLRs) by microbial products. 36,37 TLRs have been found to be critical for immune recognition and clearance of viral, bacterial, protozoan, and fungal pathogens.…”
mentioning
confidence: 99%
“…6 These data led to the hypothesis that if a Th1-mediated immune reaction to C. neoformans strain H99 in the lungs could be achieved, then infected hosts would not develop fatal central nervous system disease. 7,8 In the manuscript by Zhang et al 9 in this issue of American Journal of Pathology, the authors present data contrary to this belief. Using a murine model, Zhang et al 9 substantiated their previous findings that a Th2 immune reaction to C. neoformans strain H99 is responsible for this organism's virulence.…”
Section: Two Of the Most Commonly Studied Cd4mentioning
confidence: 86%
“…7,8 In the manuscript by Zhang et al 9 in this issue of American Journal of Pathology, the authors present data contrary to this belief. Using a murine model, Zhang et al 9 substantiated their previous findings that a Th2 immune reaction to C. neoformans strain H99 is responsible for this organism's virulence. Moreover, they established that mice deficient in two Th2 cytokines, IL-4 and IL-13, which lacked a measurable Th2 response to H99 including absence of pulmonary eosinophilia and elevated IgG, switched to a Th1 (as well as Th17) immune response and switched from alternative to classic macrophage activation.…”
Section: Two Of the Most Commonly Studied Cd4mentioning
confidence: 86%
See 1 more Smart Citation